PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN EMAS MELALUI KEPUASAN PELANGGAN DI PT. PEGADAIAN CP KALIANYAR - Yanti, Arieska Dwi (Jurnal Manajerial Bisnis, 2025)
This study aims to analyze the effect of product quality and service quality on gold purchasing decisions through customer satisfaction at PT. Pegadaian Branch Kalianyar. The background of this study focuses on the importance of product quality and service in influencing customer satisfaction and purchasing decisions. The method used in this study is a quantitative approach with data collection through questionnaires distributed to customers of PT. Pegadaian Branch Kalianyar. The collected data were then analyzed using descriptive statistical methods and SEM PLS. The results of the study indicate that product quality has a significant effect on customer satisfaction, which ultimately affects gold purchasing decisions. In addition, service quality also has a positive, although not significant, effect on customer satisfaction. These findings indicate that in order to improve customer purchasing decisions, PT. Pegadaian Branch Kalianyar needs to continue to improve the quality of products and services provided to customers.